Evaluation of anti-diarrhoeal activity in seed extracts of Mangifera indica - Sairam K.; Hemalatha S.; Kumar A.; Srinivasan T.; Ganesh J.; Shankar M.; Venkataraman S. (My University, 2025)
Mangifera indica is commonly grown in many parts of the world. Its seeds have been used for anti-diarrhoeal activity in Indian traditional medicine. This study evaluates the potential anti-diarrhoeal activity of methanolic (MMI) and aqueous (AMI) extracts of seeds of M. indica in experimental diarrhoea, induced by castor oil and magnesium sulphate in mice. Both MMI and AMI were given orally in the dose of 250 mg/kg, showed significant anti-diarrhoeal activity comparable with that of the standard drug loperamide. However, only MMI significantly reduced intestinal transit in charcoal meal test as compared with atropine sulphate (5 mg/kg; im). The in vitro antimicrobial activity of MMI and AMI showed variable results. While, AMI significantly inhibited growth of Streptococcus aureus and Proteus vulgaris, both MMI and AMI did not show any significant effect on growth of E. coli and Klebsiella. The results illustrate that the extracts of M. indica have significant anti-diarrhoeal activity and part of the activity of MMI may be attributed to its effect on intestinal transit. © 2002 Elsevier Science Ireland Ltd. All rights reserved.